The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/08998280.2018.1463040
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of stellate ganglion block for refractory angina pectoris

Abstract: Chronic refractory angina pectoris (AP) affects 600,000 to 1,800,000 Americans, with approximately 50,000 new cases annually. A recent study revealed long-term mortality of refractory AP to be lower than previously reported, with >70% of patients living >9 years. Treating AP can improve quality of life. We describe a patient with refractory AP who underwent a successful stellate ganglion block for symptom control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The conservative treatment included administration of medications, such as nonsteroidal anti-inflammatory drugs, COX-2 inhibitor, tramadol, acetaminophen, physical therapy, and soft collar immobilization. Patients with recurrent sympathetic symptoms received stellate ganglion blocks using the paravertebral technique, as described in previous studies 19–21…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conservative treatment included administration of medications, such as nonsteroidal anti-inflammatory drugs, COX-2 inhibitor, tramadol, acetaminophen, physical therapy, and soft collar immobilization. Patients with recurrent sympathetic symptoms received stellate ganglion blocks using the paravertebral technique, as described in previous studies 19–21…”
Section: Methodsmentioning
confidence: 99%
“…Patients with recurrent sympathetic symptoms received stellate ganglion blocks using the paravertebral technique, as described in previous studies. [19][20][21]…”
Section: Treatment Protocol Conservative Treatmentmentioning
confidence: 99%
“…6 SGB has a wide range of indications, including the management of complex regional pain syndrome (type I and II), hot flashes, sleep disturbance, angina, electric storm, long Q-T syndrome, ventricular tachycardia, diabetes, essential hypertension and postoperative cognitive dysfunction. [7][8][9][10] Previous studies have shown that preoperative SGB facilitates haemodynamic stabilisation during the process of anaesthesia induction, endotracheal intubation and pneumoperitoneum, and provide the beneficial effect of myocardial injury and preventing adverse cardiovascular events in high-risk patients. 11 12 Other researchers have found that SGB reduces postoperative pain,…”
Section: Introductionmentioning
confidence: 99%